PENGARUH PEMBERIAN JUS MENGKUDU TERHADAP PENURUNAN TEKANAN DARAH LANSIA DENGAN HIPERTENSI DI WILAYAH PUSKESMAS DELI TUA KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2026 - Rasninta Devi Ansela; Cahaya Artha Anastasia Gultom; Rini Debora Silalahi; Selly Febrianti (Jurnal Penelitian Keperawatan Medik, 2026)
Hypertension is a common health problem among elderly individuals and is often referred to as a silent killer because it may occur without obvious symptoms while increasing the risk of serious complications such as stroke, cardiovascular disease, and kidney failure. Aging causes physiological changes in blood vessels, including decreased arterial elasticity, which contributes to elevated blood pressure. In addition to pharmacological therapy, non-pharmacological interventions are needed to support blood pressure control. One alternative therapy is the use of noni juice (Morinda citrifolia), which contains active compounds such as scopoletin and proxeronine that have vasodilatory effects and may help reduce blood pressure This study is aimed to determine the effect of noni juice administration on blood pressure reduction among elderly patients with hypertension in the working area of Deli Tua Health Center, Deli Tua District, Deli Serdang Regency, in 2026. This study employed a quasi-experimental design with a pre-test and post-test approach involving an intervention group and a control group. The sample consisted of elderly patients with hypertension who met the inclusion and exclusion criteria. Blood pressure was measured before and after the intervention using standard measurement tools. The intervention involved administering noni juice twice daily for seven days according to the standard operating procedure. Data analysis included univariate analysis to describe respondent characteristics and blood pressure levels, and bivariate analysis using the Wilcoxon test to determine differences in blood pressure before and after the intervention. The results showed a decrease in blood pressure among elderly patients after consuming noni juice. Statistical analysis revealed a p value of 0.001 (p < 0.05), indicating a statistically significant effect of noni juice administration on blood pressure reduction in elderly patients with hypertension.